Ответы и объяснения

2014-01-28T14:32:22+04:00
4х-2\3=2(х-2\3)
4х-2\3=2х-4\3
4х-2х=-4\3+2\3
2х=-2\3
х=-2\3:2
х=-2\3*1\2
х=-1\3
Ответ:х=-1\3.
2014-01-28T14:32:39+04:00
4x+(2/3)=2(x-(2/3))4x+(2/3)= 2x-(4/3)2x=(-4/3)-(2/3)2x=(-6/3)2x=-2x=-1проверка : 4*(-1)+ (2/3)=2*((-1)-(2/3))                  -4+2/3=-2-(4/3)                      (-12/3)+(2/3)=(-6/3)-(4/3)                      -10/3=-10/3                            ч.т.д.думаю так
4x+(2/3)=2(x-(2/3))

4x+(2/3)= 2x-(4/3)

2x=(-4/3)-(2/3)

2x=(-6/3)

2x=-2

x=-1

проверка : 4*(-1)+ (2/3)=2*((-1)-(2/3))

-4+2/3=-2-(4/3)

(-12/3)+(2/3)=(-6/3)-(4/3)

-10/3=-10/3

ч.т.д.